Is normal gastric emptying a predictor of normal gastric function? - Linke, R.; Muenzing, W.; Tatsch, K. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: Impaired gastric emptying is common in many disorders. Assuming that gastric disorders primarily affect gastric peristalsis, which secondarily results in impaired emptying, the aim of our study was to evaluate whether quantitative analysis of gastric peristalsis might be a more sensitive parameter than gastric emptying to demonstrate functional gastric impairment. Patients, methods: Gastric emptying was determined scintigraphically in 141 adult (age: 18–78 years) patients (long-term Type 1 diabetes mellitus, 82 cases; systemic sclerosis, 31 cases; atrophic gastritis, 28 cases) and 20 healthy age-matched controls after ingestion of a semiliquid test meal. In addition, gastric peristalsis was evaluated by Fourier analysis of condensed images. Results: Compared to the control persons emptying was delayed in 75/141 patients, regular in 63/141 patients, and accelerated in 3/141 patients. As expected, 81% of patients with delayed emptying presented with diminished gastric contraction amplitudes. However, independent of the aetiology of the underlying disorder, 40/63 patients with regular emptying also exhibited reduced peristalsis. Conclusion: Normal gastric emptying does not predict normal gastric function. This assumption is supported by the presence of reduced amplitudes in subgroups of patients with various disorders and normal emptying. Our results suggest that the amplitude of gastric contractions may represent a more sensitive parameter for the detection of gastric dysfunction than does gastric emptying.
Keywords: Gastric dysfunction; gastric peristalsis; diabetes; systemic sclerosis; gastritis